Graduate Student Literature Review: A systematic review of articles influencing United States retail cheese packaging, labeling, and market trends related to cheese in the marketplace and during consumption* - D.A. Hutchins; R. Andrew Hurley (Journal of Dairy Science)
ABSTRACT: Innovation around cheese is constant in attempts to meet ever-increasing consumer demands. Retail packaging provides a canvas to communicate to consumers added value from innovations or inherent properties of cheese. Packaging itself may also be the subject of cheese-related innovation. This systematic review of literature organizes research over the past 10 years related to cheese packaging innovation that consumers experience in the marketplace and during consumption of cheese products. The review discusses shipping, displaying cheese at grocery stores, the value of branding, purchasing preferences by demographics, health and nutrition claims, opportunities to highlight protein in cheese, marketing to children, issues of obesity and cheese, diet cheeses, allergens and nondairy or vegan cheese, opening cheese packaging, cutting of cheese, cooking with cheese, eating cheese, the growing trend of snacking and convenience, and flavor preferences. This review provides helpful insights to cheese producers applying findings from research of various styles of cheeses, cheese marketers communicating effectively to consumers, cheese developers designing new products relevant to recent consumer demands, smaller or specialized companies seeking to differentiate their cheese product through available technology and strategy, and cheese lovers or those with hobbies surrounding food wanting to know recent advancements in cheese packaging. This review is a tool for discovering relevant articles related to cheese packaging in a marketplace and consumption setting to guide cheese and cheese packaging and labeling innovation in the United States.